The morphometric study of the normal and variant branching pattern of the Aortic arch by cadaveric dissection - Bhavana Junagade; Aruna Mukherjee (International Journal of Medical Research and Review, 2015)
Introduction: A thorough knowledge of the anatomy of the arch of aorta and its branches is of great importance today as the arch is assuming a key role in many endovascular surgeries. The varying configuration of the arch and its branching pattern are one of the main risk predictors in many endovascular surgeries such as carotid artery stenting.Methods: In the present study, the morphology and the morphometry of the aortic arch and its branches has been studied on 35 embalmed human cadavers.Results: The arch showed variant branching pattern in 11.43% cadavers. In variations, the arch was found to give rise to only 2 branches in 3 cadavers and 4 branches in 1 cadaver as against normal pattern of 3 branches. The brachiocephalic trunk, the left common carotid artery and the left subclavian artery had mean outer and inner diameters as 13.22 mm and 10.8 mm, 8.06 mm and 6 mm and 9.95 mm and 8.38 mm respectively. In 28.5% specimens the brachiocephalic trunk originated on the left of the mid-vertebral plane.Conclusion: The arch morphology is variable and becomes more so with the advancing age. Advanced non invasive radiological angiographic procedures such as, 3 dimensional CT scan or MRI have limitations in understanding actual three dimensional structure of these vessels. Thus in this era of increasing vascular invasive procedures the knowledge gained from this study will be useful to the cardiologists, cardiothoracic surgeons and radiologists in various diagnostic and therapeutic procedures, to manipulate within these vessels.